Plug in f(6) so it would be -2/3(6)+5= 1
So ur answer would be one
Answer:
y = 27.1
Step-by-step explanation:
We have the value of x:
x = 12
and we need to find the value of y in the expression:
y = x + 15.1
as we can see by the equation, the value of y depends on the value of x.
thus, we substitute x = 12 on the previous equation:
y = 12 + 15.1
y = 27.1
the value of y is 27.1
Answer:
I graphed both equations to find the solutions.
Step-by-step explanation:
When x is 0, y is -6. When x is 7, y is 8.
x = 0 and 7
Which one the first three???
Answer:
m∠ADB = 155°
Step-by-step explanation:
m∠ADB = (m∠C)/2 + 90° = 130°/2 + 90°
m∠ADB = 155°
_____
Reference brainly.com/question/17443119 for the derivation.